From Surviving to Thriving: Top Tips for Newer Chairs - Ethan Krase; Gian Pagnucci (Academic Chairpersons Conference Proceedings, 2018)
This session shares concrete strategies for helping department chairs navigate common problems more effectively and efficiently. With attention to managing email, handling complaints, constructing schedules, building relationships, and working with upper administration, the presenters offer practical tips to help newer chairs succeed.
Keywords: Practical; Scheduling; Complaints; Conflict; Email; Management